COVID-19 activities: Publicness and strategic concerns - Todd Sandler (Games, 2023)
This paper considers the diverse public good characteristics of COVID-19 activities along with their strategic implications. The underlying aggregator technologies, which relate individual contributions to the amount consumed, affect the prognosis for the supply of COVID-related activities. Weakest-link activities assume a particularly pivotal role in curbing the spread of COVID-19. For instance, the propagation of COVID-19 through new strains is disproportionately influenced by those countries with the smallest vaccination rates or least isolation actions. Diverse income distribution among at-risk countries raises the need to 'shore up' weakest-link countries' provision to lift global supply. Generally, shoring-up actions result in a Prisoner's Dilemma with unfavorable collective action prospects. As the number of countries requiring shoring up increases, the less favorable is the prospect for addressing provision shortfalls. Also, as the number of capable countries to do the shoring up increases, the prospect for successful action diminishes. The paper also examines the strategic implications of other aggregators-e.g., best shot and better shot-associated with COVID-inhibiting actions. To address best-shot anti-COVID actions, countries must pool or coordinate actions to meet a threshold. A host of institutions-e.g., the World Health Organization or public-private partnerships-can facilitate shoring-up weakest-link activities or coordinating best-shot actions.
Keywords: C72; H41; I18; 330; COVID-19; weakest-link activities; shoring up weakest-link countries; best-shot activities; provision efficiency; public policy